Organic silicon luminescent elastomer based on perovskite quantum dots and preparation method and application thereof

By adding modified ABX3 perovskite quantum dots to the X-ray imaging material, it participates in the crosslinking system, and solves the problems of perovskite quantum dot agglomeration and inter-system streaming, and achieves good mechanical and fluorescence properties of silicone luminescent elastomers.

CN119529535AActive Publication Date: 2025-02-28SHANDONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411716733.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing X-ray imaging materials use perovskite quantum dots and polymers to prepare luminescent films, resulting in agglomeration of perovskite quantum dots and intercoordinate streams, resulting in uneven luminescence and degradation of fluorescence performance.

Method used

By adding modified ABX3 perovskite quantum dots, they are involved in the crosslinking system and anchored in the crosslinking network to achieve good dispersion and stability, reduce agglomeration and streaming, and improve luminescence intensity and uniformity.

Benefits of technology

The good mechanical properties and fluorescence properties of silicone luminescent elastomers based on perovskite quantum dots are achieved, ensuring the improvement of luminescence intensity and uniformity, while maintaining good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529535A_ABST
    Figure CN119529535A_ABST
Patent Text Reader

Abstract

The invention discloses an organic silicon luminescent elastomer based on perovskite quantum dots as well as a preparation method and application thereof, and belongs to the technical field of preparation of photoluminescent elastomers. The organic silicon luminescent elastomer based on the perovskite quantum dots is prepared from the following components in parts by weight: 100 parts of base glue, 1 to 20 parts of modified ABX3 perovskite quantum dots, 10 to 60 parts of filler, 1 to 15 parts of cross-linking agent and 0.1 to 6 parts of catalyst, in the modified ABX3 perovskite quantum dot, A is Cs < + >, B is Pb < 2 + >, and X is Cl <->, Br <-> or I <->. The organic silicon luminescent elastomer based on the perovskite quantum dots, which has good mechanical properties and fluorescence properties, is obtained by making specific limits on all the components and the proportion of all the components; the modified ABX3 perovskite quantum dots are added, so that the modified ABX3 perovskite quantum dots can participate in a cross-linking system, are effectively anchored in a cross-linking network and have good dispersity and stability, agglomeration and intersystem streaming of the perovskite quantum dots are reduced, and good luminous intensity, luminous uniformity and continuity are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a perovskite quantum dot-based organosilicon luminescent elastomer and a preparation method and application thereof, belonging to the technical field of photoluminescent elastomer preparation. Background Art

[0002] In the field of X-ray imaging, traditional inorganic alkali halide scintillators (such as commercial CsI:Tl) have problems such as high toxicity and high detection limits, and usually require high temperature preparation and are difficult to use in flexible devices. New organic long afterglow scintillators can be processed in solution, but have low luminescence efficiency, and their long luminescence lifetime easily leads to slow response speed of X-ray imaging.

[0003] In recent years, perovskite quantum dots have been widely used in solar cells, light-emitting diodes, photodetectors, lasers, etc. due to their high absorption coefficient, high quantum yield and low preparation cost. More importantly, perovskite quantum dots have heavy atoms and large electron-hole extension length, which can be used in X-ray imaging.

[0004] Existing X-ray imaging materials use perovskite quantum dots, which are mixed with polymers such as polystyrene by physical mixing and then cured to obtain a luminescent film. However, the luminescent film prepared by the above method will show agglomeration and inter-system cross-talk of perovskite quantum dots in the polymer. On the one hand, the agglomeration of perovskite quantum dots will lead to uneven luminescence of the luminescent film; on the other hand, the fluorescence performance of perovskite quantum dots will be reduced due to agglomeration quenching, resulting in reduced fluorescence intensity, reduced fluorescence duration, and reduced fluorescence uniformity. Summary of the invention

[0005] In order to solve the above problems, a perovskite quantum dot-based organosilicon luminescent elastomer and a preparation method and application thereof are provided. By making specific restrictions on the components and the proportions of the components, a perovskite quantum dot-based organosilicon luminescent elastomer with good mechanical properties and fluorescence properties is obtained. By adding modified ABX3 perovskite quantum dots, it is enabled to participate in the cross-linking system and be effectively anchored in the cross-linking network, and has good dispersibility and stability, reducing the agglomeration of perovskite quantum dots and inter-system cross-flow, so as to achieve good luminescence intensity and luminescence uniformity and continuity.

[0006] According to one aspect of the present application, a perovskite quantum dot-based organosilicon luminescent elastomer is provided, which comprises the following components by weight: 100 parts of base glue, 1 to 20 parts of modified ABX3 perovskite quantum dots, 10 to 60 parts of fillers, 1 to 15 parts of crosslinking agents and 0.1 to 6 parts of catalysts; wherein A in the modified ABX3 perovskite quantum dots is Cs +, B=Pb 2+ , X=Cl - Br - or I - .

[0007] The modified ABX3 perovskite quantum dots have high photoluminescence quantum efficiency, narrow emission peak, high color purity, and the emission spectrum can be adjusted by regulating anions; they also have better thermal stability and moisture resistance, and can be compatible with the silicone luminescent elastomer system.

[0008] Specifically, the application makes specific restrictions on the weight ratio of base glue, modified ABX3 perovskite quantum dots, fillers, crosslinkers and catalysts to obtain silicone luminescent elastomers with excellent mechanical properties and fluorescence properties. Among them, as the weight ratio of fillers increases, the strength of silicone luminescent elastomers based on perovskite quantum dots increases, but if too much filler is added, it is difficult to mix evenly with the base glue; the crosslinker provides crosslinking points in the polymer reaction process, so that the linear polymer can form a three-dimensional crosslinked network structure, so that the modified ABX3 perovskite quantum dots are effectively anchored in the crosslinked network, but too many crosslinking points will have an adverse effect on the mechanical properties; adding a specific number of catalysts can trigger a crosslinking reaction, increase the curing speed, and shorten the curing time.

[0009] Specifically, the present application sets a limit on the amount of modified ABX3 perovskite quantum dots added. If too little is added, the fluorescence performance will deteriorate, but if too much is added, a second phase will be formed in the polymer matrix, which seriously affects the initial mechanical properties and greatly reduces the tensile strength.

[0010] Preferably, the following components are included in parts by weight: 100 parts of base glue, 3 to 15 parts of modified ABX3 perovskite quantum dots, 20 to 40 parts of filler, 2 to 8 parts of cross-linking agent and 0.1 to 3 parts of catalyst.

[0011] Optionally, the modified ABX3 perovskite quantum dots are ABX3 perovskite quantum dots modified by organic silicon polymer.

[0012] Specifically, silicone polymers are based on repeated Si-O bonds as the main chain, with organic groups attached to silicon atoms. Due to the flexibility of the Si-O main chain, silicone polymers have good flexibility, as well as unique physical and chemical properties such as high and low temperature resistance, aging resistance, physiological inertness, and ozone resistance.

[0013] Specifically, the ABX3 perovskite quantum dots modified with silicone polymers, i.e., modified ABX3 perovskite quantum dots, have better fluorescence intensity and better compatibility, avoiding the occurrence of a decrease in mechanical properties caused by problems such as phase separation.

[0014] Optionally, the organic silicon polymer includes a hydroxyl-terminated mercapto polysiloxane, a hydroxyl-terminated trifluoropropyl polysiloxane, a hydroxyl-terminated amino polysiloxane or a hydroxyl-terminated carboxyl polysiloxane.

[0015] The molecular weight of the organic silicon polymer is 1,000 to 20,000.

[0016] If the molecular weight of the silicone polymer is less than 1000, the functional groups of the silicone polymer coordinated with the ABX3 perovskite quantum dots are too few and the modification effect is not obvious; if the molecular weight is greater than 20,000, the solubility of the silicone polymer in the solvent becomes poor, making it difficult to effectively passivate the perovskite quantum dots.

[0017] Specifically, silicone polymers can introduce thiol, carboxyl, amino and other groups, which can effectively passivate the surface defects of ABX3 perovskite quantum dots and have higher adsorption energy, so the stability of ABX3 perovskite quantum dots will be effectively improved; in addition, the perovskite quantum dots modified by silicone polymers have better compatibility with silicone rubber and better dispersibility in the polymer matrix.

[0018] Optionally, the base rubber is a hydroxyl-terminated polysiloxane or a dihydroxy polysiloxane; the filler is one or more of fumed silica, precipitated silica, calcium carbonate or talc; the cross-linking agent is a silane coupling agent with trifunctionality or above of silylmethoxy or silylethoxy; and the catalyst is at least one of dibutyltin dilaurate and stannous octoate.

[0019] Specifically, the base glue includes one of α, ω-dihydroxy polydimethylsiloxane, α, ω-dihydroxy poly (dimethyl, diphenyl) siloxane, α, ω-dihydroxy poly (dimethyl, methylphenyl) siloxane or α, ω-dihydroxy polymethyl trifluoropropyl siloxane.

[0020] Specifically, the crosslinking agent includes one or more of tetraethyl silicate, polyethyl silicate or methyltriethoxysilane.

[0021] Preferably, the gum base is α,ω-dihydroxypolydimethylsiloxane.

[0022] Preferably, the molecular weight of the α,ω-dihydroxypolydimethylsiloxane is 5,000 to 40,000.

[0023] Optionally, the method for preparing the modified ABX3 perovskite quantum dots comprises the following steps:

[0024] S1 adds the organosilicon polymer to the ABX3 perovskite quantum dot solution and stirs the reaction;

[0025] S2 was centrifuged, the supernatant was discarded, and the precipitate was collected to obtain the modified ABX3 perovskite quantum dots.

[0026] Optionally, the mass ratio of the ABX3 perovskite quantum dots to the organosilicon polymer is 1:0.05-10; the stirring reaction time in S1 is 10-60 min; the centrifugal speed in S2 is 6000-15000 rpm; and the centrifugal time is 5-30 minutes.

[0027] Specifically, the mass ratio of the ABX3 perovskite quantum dots to the organosilicon polymer is 1:0.5-5.

[0028] Specifically, the concentration of the ABX3 perovskite quantum dots is 0.001 to 0.1 mmol / mL.

[0029] Specifically, the solvent in the ABX3 perovskite quantum dot solution is one or more of acetone, butanone, cyclohexanone, dichloromethane, chloroform, n-hexane, and ethyl acetate.

[0030] Optionally, the method for preparing the ABX3 perovskite quantum dots comprises the following steps:

[0031] (1) adding cesium halide, lead halide and polar solvent into a beaker and completely dissolving them to obtain a mixed solution;

[0032] (2) adding ligand A and ligand B to the mixed solution, and sonicating until they are completely dissolved to obtain a precursor solution;

[0033] (3) adding the precursor solution into a rapidly stirred non-polar solvent to react and obtain a solution;

[0034] (4) Centrifuging, discarding the supernatant, collecting the precipitate, and obtaining ABX3 perovskite quantum dots.

[0035] Optionally, the cesium halide is one or more of cesium chloride, cesium bromide, and cesium iodide, and the lead halide is one or more of lead chloride, lead bromide, and lead iodide; the molar ratio of the cesium halide to the lead halide is 1:1; the ligand A is at least one of an organic carboxylic acid ligand and an organic phosphoric acid ligand; the ligand B is at least one of an organic primary amine ligand, an organic secondary amine ligand, and an organic tertiary amine ligand; the molar ratio of the ligand A to the ligand B is 1:0.1 to 10; the sum of the masses of the cesium halide and the lead halide is 0.05 to 5 times the sum of the masses of the ligand A and the ligand B.

[0036] Specifically, the molar ratio of cesium halide to lead halide is 1:1 to generate ABX3 perovskite quantum dots with a three-dimensional structure.

[0037] Specifically, ligand A includes organic small molecules with carboxyl groups such as oleic acid, octyl phosphate, deoxy phosphate, octadecanoic acid, hexadecanoic acid, etc.; ligand B includes organic small molecules with amino groups such as oleylamine, octadecylamine, hexadecylamine, dodecylamine, etc.

[0038] Preferably, the sum of the masses of the cesium halide and the lead halide is 4 times the sum of the masses of the ligand A and the ligand B.

[0039] Specifically, the polar solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, ethanol and chloroform; the non-polar solvent is one or more of acetone, butanone, cyclohexanone, toluene, dichloromethane, chloroform, n-hexane and ethyl acetate.

[0040] According to another aspect of the present application, the present application also provides a method for preparing the above-mentioned organosilicon luminescent elastomer based on perovskite quantum dots, comprising the following steps:

[0041] The modified ABX3 perovskite quantum dots are fully mixed with the base glue, crosslinking agent, filler and catalyst, poured into a mold, and vulcanized under natural environment conditions to obtain a silicone luminescent elastomer based on perovskite quantum dots.

[0042] Specifically, the mold is a polytetrafluoroethylene mold.

[0043] According to another aspect of the present application, the present application also provides the use of the above-mentioned perovskite quantum dot-based organosilicon luminescent elastomer or the perovskite quantum dot-based organosilicon luminescent elastomer prepared by the above-mentioned preparation method in the preparation of X-ray imaging.

[0044] Specifically, the above-mentioned organosilicon luminescent elastomer based on perovskite quantum dots can be used to prepare an X-ray imaging screen, which can be used in medical diagnosis, public security inspection, maintenance of chip internal circuits and other fields.

[0045] The beneficial effects of this application include but are not limited to:

[0046] 1. According to the perovskite quantum dot-based organosilicon luminescent elastomer of the present application, by making specific restrictions on the components and the proportions of the components, a perovskite quantum dot-based organosilicon luminescent elastomer with good mechanical properties and fluorescence properties is obtained; by adding modified ABX3 perovskite quantum dots, it is enabled to participate in the cross-linking system, effectively anchored in the cross-linking network, and has good dispersibility and stability, reducing the agglomeration of perovskite quantum dots and inter-system cross-flow, so as to achieve good luminescence intensity and luminescence uniformity and continuity.

[0047] 2. According to the organosilicon luminescent elastomer based on perovskite quantum dots of the present application, the preparation method of the modified ABX3 perovskite quantum dots is specifically defined, and the reactants and the addition ratio of the reactants are specifically defined. The ABX3 perovskite quantum dots are passivated and modified by using an organosilicon polymer. On the one hand, the organosilicon polymer is non-toxic and harmless, resistant to high and low temperatures, weather-resistant and has good flexibility; on the other hand, the organosilicon luminescent elastomer system forms a cross-linked network through hydroxyl condensation, and the organosilicon polymer modifies the ABX3 perovskite quantum dots, introduces thiol, carboxyl or amino groups, and the active groups on the passivated modified perovskite quantum dots enable the passivated modified perovskite quantum dots to better participate in the cross-linking system of the organosilicon polymer, which is conducive to dispersion and stability; the modified ABX3 perovskite quantum dots have better fluorescence intensity and better compatibility, avoiding the occurrence of mechanical property degradation caused by problems such as phase separation.

[0048] 3. According to the preparation method of the perovskite quantum dot-based organosilicon luminescent elastomer of the present application, the preparation method is simple, can be carried out under natural environment conditions, and the raw materials are easily available, which is convenient for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0050] Figure 1 This is a transmission electron microscope image of the perovskite quantum dots involved in Example 1 of the present application.

[0051] Figure 2 These are pictures of the perovskite quantum dot-based organosilicon luminescent elastomers involved in Examples 1 to 4 of the present application.

[0052] Figure 3 The perovskite quantum dot-based organosilicon luminescent elastomer involved in Example 1 of the present application is used as an X-ray imaging screen to take pictures of electronic chips. DETAILED DESCRIPTION

[0053] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0054] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.

[0055] Example 1

[0056] (1) Add 0.2 mmol of cesium bromide, 0.2 mmol of lead bromide and 5 mL of N,N-dimethylformamide into a beaker and completely dissolve them to obtain a mixed solution;

[0057] (2) adding 1.77 mmol oleic acid and 1.87 mmol g oleylamine to the mixed solution, and sonicating until completely dissolved to obtain a precursor solution;

[0058] (3) adding 1 ml of the precursor solution into a rapidly stirred toluene solvent and reacting for 5 minutes to obtain a solution;

[0059] (4) centrifuging at 12000 rpm for 10 minutes in a high-speed centrifuge, discarding the supernatant, collecting the precipitate, and obtaining CsPbBr3 perovskite quantum dots;

[0060] (5) taking 1 g of CsPbBr3 perovskite quantum dots, adding 0.2 g of hydroxyl-terminated aminopolysiloxane (number average molecular weight 3900) to a rapidly stirred acetone solution of perovskite quantum dots, wherein the concentration of CsPbBr3 perovskite quantum dots in the acetone solution of perovskite quantum dots is 0.01 mmol / ml, reacting for 20 min, centrifuging, discarding the supernatant, collecting the precipitate, and obtaining modified perovskite quantum dots;

[0061] (6) 10 parts of modified perovskite quantum dots, 100 parts of base rubber α, ω-dihydroxypolydimethylsiloxane (number average molecular weight 6000), 4 parts of crosslinking agent tetraethyl silicate, 20 parts of filler fumed silica and 0.5 parts of catalyst dibutyltin dilaurate were fully mixed, poured into a polytetrafluoroethylene mold, and vulcanized under natural environment conditions to obtain a silicone luminescent elastomer based on perovskite quantum dots.

[0062] Example 2

[0063] (1) 0.13 mmol of cesium bromide, 0.067 mmol of cesium iodide, 0.13 mmol of lead bromide, 0.067 mmol of lead iodide, and 5 mL of dimethyl sulfoxide were added into a beaker and completely dissolved to obtain a mixed solution;

[0064] (2) adding 1.77 mmol oleic acid and 1.87 mmol oleylamine to the mixed solution, and sonicating until completely dissolved to obtain a precursor solution;

[0065] (3) adding 1 ml of the precursor solution into a rapidly stirred acetone solvent and reacting for 5 minutes to obtain a solution;

[0066] (4) centrifuging at 12000 rpm for 10 min in a high-speed centrifuge, discarding the supernatant, collecting the precipitate, and obtaining CsPbBr2I1 perovskite quantum dots;

[0067] (5) taking 1 g of CsPbBr2I1 perovskite quantum dots, adding 0.2 g of hydroxyl-terminated mercapto polysiloxane (number average molecular weight 2100) to a rapidly stirred perovskite quantum dot butanone solution, wherein the concentration of CsPbBr2I1 perovskite quantum dots in the perovskite quantum dot butanone solution is 0.1 mmol / ml, reacting for 20 min, centrifuging, discarding the supernatant, collecting the precipitate, and obtaining modified perovskite quantum dots;

[0068] (6) 10 parts of modified perovskite quantum dots, 100 parts of base rubber α, ω-dihydroxypolydimethylsiloxane (number average molecular weight 6000), 4 parts of crosslinking agent tetraethyl silicate, 20 parts of filler fumed silica and 0.5 parts of catalyst dibutyltin dilaurate were fully mixed, poured into a polytetrafluoroethylene mold, and vulcanized under natural environment conditions to obtain a silicone luminescent elastomer based on perovskite quantum dots.

[0069] Example 3

[0070] (1) adding 0.1 mmol of cesium bromide, 0.1 mmol of cesium iodide, 0.1 mmol of lead bromide, 0.1 mmol of lead iodide and 5 mL of N,N-dimethylformamide into a beaker and completely dissolving them to obtain a mixed solution;

[0071] (2) adding 0.17 mmol oleic acid and 0.18 mmol oleylamine to the mixed solution, and sonicating until completely dissolved to obtain a precursor solution;

[0072] (3) adding 1 ml of the precursor solution into a rapidly stirred dichloromethane solvent and reacting for 5 minutes to obtain a solution;

[0073] (4) Centrifuge at 12000 rpm for 10 minutes, discard the supernatant, collect the precipitate, and obtain CsPbBr 1.5 I 1.5 Perovskite quantum dots;

[0074] (5) Take 1gCsPbBr 1.5 I 1.5 Perovskite quantum dots, 0.2 g of hydroxyl-terminated carboxyl polysiloxane (number average molecular weight 3700) was added to the rapidly stirred perovskite quantum dot solution. 1.5 I 1.5 The concentration of perovskite quantum dots was 0.01 mmol / ml, and the reaction was centrifuged after 20 min, the supernatant was discarded, and the precipitate was collected to obtain modified perovskite quantum dots;

[0075] (6) 10 parts of modified perovskite quantum dots, 100 parts of base rubber α, ω-dihydroxypolydimethylsiloxane (number average molecular weight 6000), 4 parts of crosslinking agent tetraethyl silicate, 20 parts of filler fumed silica and 0.5 parts of catalyst dibutyltin dilaurate were fully mixed, poured into a polytetrafluoroethylene mold, and vulcanized under natural environment conditions to obtain a silicone luminescent elastomer based on perovskite quantum dots.

[0076] Example 4

[0077] (1) 0.067 mmol of cesium bromide, 0.13 mmol of cesium iodide, 0.067 mmol of lead bromide, 0.13 mmol of lead iodide, and 5 mL of N,N-dimethylformamide were added into a beaker and completely dissolved to obtain a mixed solution;

[0078] (2) adding 0.0585 mmol oleic acid and 0.0585 mmol oleylamine to the mixed solution, and sonicating until completely dissolved to obtain a precursor solution;

[0079] (3) adding 1 ml of the precursor solution into a rapidly stirred butanone solvent and reacting for 5 minutes to obtain a solution;

[0080] (4) centrifuging at 12000 rpm for 10 min in a high-speed centrifuge, discarding the supernatant, collecting the precipitate, and obtaining CsPbBr1I2 perovskite quantum dots;

[0081] (5) taking 1 g of CsPbBr1I2 perovskite quantum dots, adding 0.2 g of hydroxyl-terminated trifluoropropyl polysiloxane (number average molecular weight 1800) to a rapidly stirred CsPbBr1I2 perovskite quantum dot solution, wherein the concentration of CsPbBr1I2 perovskite quantum dots in the acetone solution of perovskite quantum dots is 0.01 mmol / ml, reacting for 20 min, centrifuging, discarding the supernatant, collecting the precipitate, and obtaining CsPbBr1I2 modified perovskite quantum dots;

[0082] (6) 10 parts of modified perovskite quantum dots, 100 parts of base rubber α, ω-dihydroxypolydimethylsiloxane (number average molecular weight 6000), 4 parts of crosslinking agent tetraethyl silicate, 20 parts of filler fumed silica and 0.5 parts of catalyst dibutyltin dilaurate were fully mixed, poured into a polytetrafluoroethylene mold, and vulcanized under natural environment conditions to obtain a silicone luminescent elastomer based on perovskite quantum dots.

[0083] Example 5

[0084] The difference between Example 5 and Example 1 is that in step (2), ligand A is 0.00739 mmol octadecanoic acid, and ligand B is 0.0739 mmol octadecylamine; in step (5), the mass ratio of perovskite quantum dots to hydroxyl-terminated aminopolysiloxane is 1:10; and step (6) includes 100 parts of base glue, 20 parts of modified ABX3 perovskite quantum dots, 60 parts of filler, 15 parts of cross-linking agent and 6 parts of catalyst.

[0085] Example 6

[0086] The difference between Example 6 and Example 1 is that in step (2), ligand A is 7.64 mmol oleic acid and ligand B is 0.764 mmol oleylamine; in step (5), the mass ratio of perovskite quantum dots to hydroxyl-terminated aminopolysiloxane is 1:0.05; and step (6) includes 100 parts of base glue, 1 part of modified ABX3 perovskite quantum dots, 10 parts of filler, 1 part of cross-linking agent and 0.1 part of catalyst.

[0087] Example 7

[0088] The difference between Example 7 and Example 1 is that the number average molecular weight of the organic silicon polymer in step (5) is 20,000, the number average molecular weight of the α, ω-dihydroxypolydimethylsiloxane in step (6) is 40,000, and the rest are the same.

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 1 is that the ABX3 perovskite quantum dots used are not modified, and the rest are the same.

[0091] Comparative Example 2

[0092] The difference between Comparative Example 2 and Example 1 is that the perovskite quantum dots are MAPbI3 perovskite quantum dots, and the rest are the same.

[0093] Comparative Example 3

[0094] The difference between Comparative Document 3 and Example 1 is that the amount of modified ABX3 perovskite quantum dots added is 30 parts, and the rest is the same.

[0095] Experimental Example 1

[0096] The performance of the organosilicon luminescent elastomer based on perovskite quantum dots prepared in the above Examples 1 to 7 and Comparative Examples 1 to 3 was tested. The test results are shown in Table 1.

[0097] Table 1 Performance test results

[0098] Group Tensile Strength Elongation Initial luminous intensity Luminous intensity after 48 hours Example 1 2.67MPa 310% 100% 90% Example 2 2.54MPa 296% 100% 85% Example 3 2.65MPa 284% 100% 87% Example 4 2.71MPa 306% 100% 91% Example 5 3.21MPa 282% 100% 88% Example 6 2.16MPa 184% 100% 89% Example 7 2.97MPa 320% 100% 92% Comparative Example 1 2.01MPa 218% 100% 32% Comparative Example 2 2.54MPa 267% 100% 14% Comparative Example 3 1.46MPa 167% 100% 82%

[0099] According to Table 1, the organosilicon luminescent elastomers based on perovskite quantum dots obtained in Examples 1 to 7 have excellent mechanical properties and fluorescence properties. The luminescence intensity can reach more than 85% after 48 hours. In Example 7, the luminescence intensity can reach 92% after 48 hours, and has good luminescence stability. The tensile strength and elongation of Examples 1 to 7 are also significantly improved compared with Comparative Examples 1 to 3. Among them, the ABX3 perovskite quantum dots used in Comparative Example 1 are not modified, and the tensile strength, elongation and luminescence intensity after 48 hours of the obtained organosilicon luminescent elastomer based on perovskite quantum dots are significantly decreased. The reason for analysis is that the unmodified ABX3 perovskite quantum dots have poor compatibility and fluorescence intensity stability, resulting in a significant decrease in the tensile strength of the organosilicon luminescent elastomer based on perovskite quantum dots; the perovskite quantum dots in Comparative Example 2 are MAPbI3 perovskite quantum dots, and the luminescence intensity of the organosilicon luminescent elastomer based on perovskite quantum dots is significantly decreased after 48 hours. The reason for analysis is that the MAPbI3 perovskite quantum dots have poor stability and the luminescence duration is greatly reduced; in Comparative Example 3, the amount of modified ABX3 perovskite quantum dots added is 30 parts, and its mechanical properties and fluorescence properties are affected. The reason for analysis is that the amount of modified ABX3 perovskite quantum dots added is too much, resulting in the formation of a second phase in the polymer matrix, which seriously affects the initial mechanical properties, greatly reduces the tensile strength, and also affects the fluorescence properties.

[0100] according to Figure 1 to Figure 3 , Figure 1 This is a transmission electron microscope image of the perovskite quantum dots involved in Example 1 of the present application. It can be seen that the obtained perovskite quantum dots are very uniform in size and are in a cubic phase. Figure 2 These are pictures of the perovskite quantum dot-based organosilicon luminescent elastomers involved in Examples 1 to 4 of the present application. By adjusting the ratio of halogen anions, organosilicon luminescent elastomers based on perovskite quantum dots of different colors can be obtained. Figure 3 The organosilicon luminescent elastomer based on perovskite quantum dots involved in Example 1 of the present application is used as an X-ray imaging screen to take pictures of electronic chips. The picture shows that the prepared organosilicon luminescent elastomer film based on perovskite quantum dots has very uniform fluorescence and high brightness, and has good luminescent properties.

[0101] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A perovskite quantum dot-based organosilicon luminescent elastomer, characterized in that: The invention comprises the following components in parts by weight: 100 parts of base glue, 1 to 20 parts of modified ABX3 perovskite quantum dots, 10 to 60 parts of fillers, 1 to 15 parts of crosslinking agents and 0.1 to 6 parts of catalysts; wherein A in the modified ABX3 perovskite quantum dots is Cs + , B=Pb 2+ , X=Cl - Br - or I - .

2. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 1, characterized in that: The modified ABX3 perovskite quantum dots are obtained by modifying the ABX3 perovskite quantum dots with an organic silicon polymer.

3. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 1, characterized in that: The organic silicon polymer includes a hydroxyl-terminated mercapto polysiloxane, a hydroxyl-terminated trifluoropropyl polysiloxane, a hydroxyl-terminated amino polysiloxane or a hydroxyl-terminated carboxyl polysiloxane.

4. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 1, characterized in that: The base rubber is hydroxyl-terminated polysiloxane or dihydroxy polysiloxane; the filler is one or more of fumed silica, precipitated silica, calcium carbonate or talcum powder; the cross-linking agent is a silane coupling agent with trifunctionality or above of silylmethoxy or silylethoxy; the catalyst is at least one of dibutyltin dilaurate and stannous octoate.

5. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 1, characterized in that: The preparation method of the modified ABX3 perovskite quantum dots comprises the following steps: S1 adds the organosilicon polymer to the ABX3 perovskite quantum dot solution and stirs the reaction; S2 was centrifuged, the supernatant was discarded, and the precipitate was collected to obtain the modified ABX3 perovskite quantum dots.

6. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 5, characterized in that: The mass ratio of the ABX3 perovskite quantum dots to the organosilicon polymer is 1:0.05-10; the stirring reaction time in S1 is 10-60 minutes; the centrifugal speed in S2 is 6000-15000 rpm; and the centrifugal time is 5-30 minutes.

7. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 1, characterized in that: The preparation method of the ABX3 perovskite quantum dots comprises the following steps: (1) adding cesium halide, lead halide and polar solvent into a beaker and completely dissolving them to obtain a mixed solution; (2) adding ligand A and ligand B to the mixed solution, and sonicating until they are completely dissolved to obtain a precursor solution; (3) adding the precursor solution into a rapidly stirred non-polar solvent to react and obtain a solution; (4) Centrifuging, discarding the supernatant, collecting the precipitate, and obtaining ABX3 perovskite quantum dots.

8. The organosilicon luminescent elastomer based on perovskite quantum dots according to claim 7, characterized in that: The cesium halide is one or more of cesium chloride, cesium bromide, and cesium iodide, and the lead halide is one or more of lead chloride, lead bromide, and lead iodide; the molar ratio of the cesium halide to the lead halide is 1:1; the ligand A is at least one of an organic carboxylic acid ligand and an organic phosphoric acid ligand; the ligand B is at least one of an organic primary amine ligand, an organic secondary amine ligand, and an organic tertiary amine ligand; the molar ratio of the ligand A to the ligand B is 1:0.1-10; the sum of the masses of the cesium halide and the lead halide is 0.05-5 times the sum of the masses of the ligand A and the ligand B.

9. The method for preparing a perovskite quantum dot-based organosilicon luminescent elastomer according to any one of claims 1 to 8, characterized in that: The following steps are involved: The modified ABX3 perovskite quantum dots are fully mixed with the base glue, crosslinking agent, filler and catalyst, poured into a mold, and vulcanized under natural environment conditions to obtain a silicone luminescent elastomer based on perovskite quantum dots.

10. Use of the organosilicone luminescent elastomer based on perovskite quantum dots according to any one of claims 1 to 8 or the organosilicone luminescent elastomer based on perovskite quantum dots prepared by the preparation method of claim 9 in the preparation of X-ray imaging.

Citation Information

Patent Citations

  • Preparation method for lead halide caesium perovskite quantum dot colloid and quantum dot fluorescent powder

    CN109266343A

  • Red and green light perovskite quantum dot stable fluorescent powder based on SiO2 coating and preparation

    CN110872510A

  • Method for preparing cesium-lead halide perovskite quantum dots based on in-situ mercaptosilane passivation

    CN112251221A

  • Quantum dot light-emitting device, light-emitting layer, preparation method and display device

    CN113328041A

  • Preparation method of organic silicon-perovskite composite material

    CN115260502A